The Development of Scratch Software-Based Interactive Learning Media on Regulatory System Material - Nurhalizah, Nurhalizah; Jayanti, Ummi Nur Afinni Dwi (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2023)
The research aims to develop interactive learning media based on software scratch on the material of the regulatory system and to know the validity, practicality, and efficacy of the media. The research and development method with the ADDIE model is used in this research. The research instruments used are needs analysis in the form of teacher interview guides and student questionnaires, validation sheets consisting of media and materials expert validation sheets, and implementation tools in the form of effectiveness sheets, namely pre-test and post-test, and practicality sheets, namely teacher and student response questionnaires. Based on the results and discussion, the media expert`s validity test result is 87.33%, and the material expert's result is 87.50%, indicating that it is very valid. Then, the practicality test results of the teacher's responses received a percentage of 97.50%, which is very practical. The practicality test of student responses on a small scale yielded a rate of 93.25%, which is very practical, while the field test yielded a rate of 84.30%, which is quite practical. In the effectiveness test, the percentage of n-gain obtained was 84%, which means it was effective. The results show that scratch-based interactive learning media have proven to be valid, practical, and effective. This learning media can be implied as one of the supporting media for teachers in biology subjects, particularly on regulatory system material that may boost students' motivation for learning and academic success.